Problems and Countermeasures of the Integration of Information Technology and English Curriculum in Secondary Vocational Schools - Li, Congcong (Journal of Theory and Practice of Contemporary Education, 2024)
With the development of information technology, information teaching has become an important teaching method. The theory and practice of information-based teaching have become increasingly rich, and the technical means have become increasingly diversified. At present, the focus of the research has shifted from focusing on the construction of hardware, software and resources to focusing on the effectiveness of the application of information technology in schools and classrooms, that is, the effect, efficiency and efficiency of information teaching. This paper gives some opinions on how to realize the effective integration of information technology and secondary vocational English curriculum and the corresponding countermeasures. For a long time, mankind has been faced with the problem of global poverty, and the United Nations has also listed "eradicating poverty in all forms in the world" as the primary goal of the 2030 Agenda for Sustainable Development. Eliminating poverty, improving people's livelihood and gradually realizing common prosperity are the essential requirements of socialism [1]. Poverty alleviation has always been highly valued by the Party Central Committee and the fundamental task of building a well-off society. The strategic idea of "targeted poverty reduction" was first proposed by Xi Jinping in 2013; Since then, the concept of targeted poverty reduction has become increasingly mature, providing an important reference for poverty reduction in developing countries. At the National Poverty Alleviation Work Summary and Commendation Conference in 2020, Xi Jinping announced that at present, 98.99 million people in poor rural areas in China have achieved comprehensive poverty eradication and the goal of eliminating "absolute poverty"